1999
DOI: 10.1046/j.1471-4159.1999.0731066.x
|View full text |Cite
|
Sign up to set email alerts
|

The K‐Opioid Agonist, U‐69593, Decreases Acute Amphetamine‐Evoked Behaviors and Calcium‐Dependent Dialysate Levels of Dopamine and Glutamate in the Ventral Striatum

Abstract: Abstract:The effects of a -opioid receptor agonist on acute amphetamine-induced behavioral activation and dialysate levels of dopamine and glutamate in the ventral striatum were investigated. Amphetamine (2.5 mg/kg i.p.) evoked a substantial increase in rearing, sniffing, and hole-poking behavior as well as dopamine and glutamate levels in the ventral striatum of awake rats. U-69593 (0.32 mg/kg s.c.) significantly decreased the amphetamineevoked increase in behavior and dopamine and glutamate levels in the ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 42 publications
8
83
0
Order By: Relevance
“…The observation that an effect of amphetamine administration can be mimicked by KOP receptor agonists appears paradoxical to several studies showing that KOP receptor agonists prevent many of the behavioral effects of amphetamine (Gray et al, 1999;Tzaferis and McGinty, 2001). However, these immediate effects of KOP receptor stimulation can be distinguished from their longer-lasting modulatory effects on the endogenous opioid system.…”
Section: Discussionmentioning
confidence: 94%
“…The observation that an effect of amphetamine administration can be mimicked by KOP receptor agonists appears paradoxical to several studies showing that KOP receptor agonists prevent many of the behavioral effects of amphetamine (Gray et al, 1999;Tzaferis and McGinty, 2001). However, these immediate effects of KOP receptor stimulation can be distinguished from their longer-lasting modulatory effects on the endogenous opioid system.…”
Section: Discussionmentioning
confidence: 94%
“…U50,488H and U69,593, commonly used in microdialysis studies. When given alone, U50,488H (You et al, 1999) and U69,593 (Rawls and McGinty, 1998;Gray et al, 1999), do not affect glutamate levels within the striatum. We are first to confirm, through microdialysis, that the clinically useful kappa receptor agonist, nalfurafine, does not affect glutamate levels in the striatum.…”
Section: Discussionmentioning
confidence: 96%
“…Since activation of kappa opioid receptors decreases glutamate release intrastriatally (Hill and Brotchie, 1995;Rawls and McGinty, 1998;Gray et al, 1999;Hill and Brotchie, 1999; and extrastriatally (Gannon and Terrian, 1992;Maneuf et al, 1995;Sbrenna et al, 1999), we cannot establish how icilin acts to increase glutamate levels in the dorsal striatum or how a kappa agonist, like nalfurafine, reverses the behavioral or neurochemical action of icilin in rats. Although we have shown that icilin increases glutamate release we have not observed overt seizures in rats following intraperitoneal, intrastriatal or intracerebroventricular injection of icilin (data not shown).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations